ANALISIS LAPORAN KEUANGAN DALAM MENILAI KINERJA PT. INDOFOOD CBP SUKSES MAKMUR TBK. - Alfonsius Deri; Martinus Robert Hutauruk; Pantas Pangondian Pardede (OBOR: Oikonomia Borneo, 2019)
The purpose of this study is to determine the financial performance of PT Indofood CBP SuksesMakmur Tbk from 2014-2018 using financial ratios. The results of the discussion of financial ratios used are liquidity ratios consisting of ratios Current Ratio and Ouick Ratio. Then the Solvency Ratio consists of Debt To Asset Ratio and Debt To Equity Ratio ratios. Activity ratio consists of Fixed Asset Tun Over ratio, and Total Asset Turn Over. Then the Profitability Ratio consists of the ratio of Return On Assets, and Return On Equity. The results of this study indicate that the company performs well when viewed from the liquidity ratio and solvency ratio. While the average is not good when seen from the ratio of profitability and activity. Keywords : Liquidity, Solvency. Profitability, Activity